Quantum mechanics 2 - Green, Nicholas ([S.l.] : Oxford University Press, 1998)
The chemist's approach to the understanding of matter and its chemical transformations is to take a microscopic view, connecting experimental observation with the properties of the constituent molecules. Atoms and sub-atomic particles do not obey the classical laws of mechanics but conform rather to the laws of quantum mechanics. Quantum mechanics is thus of central importance in chemistry. In order to understand the behavior of molecules and their constituent particles it is necessary to have a thorough grounding in the principles and applications of quantum mechanics. Quantum Mechanics 2: The Toolkit provides a toolkit for applying quantum mechanics to chemical problems, introducing more advanced approaches using approximate methods. It describes areas of chemistry where quantum mechanics is important, and shows how quantum mechanics can be applied to chemical problems.
Keywords: quantum mechanics